Impacto económico de la plataforma Airbnb como desarrollo para el sector turístico de la ciudad de Santa Marta (2024)
Santa Marta is a city of opportunities, this goes beyond offering its visitors and citizens beaches and destinations to enjoy, without imagining that this factor makes it a significant city, which after this could generate economic benefits for families, students , professionals, families with independent and informal jobs and occasionally companies that operate in tourism. But what is this digital platform that is transforming the city's cultural economy and what financial options does it have to prosper and be genuinely profitable? Anyone who travels the world today is aware of Airbnb, a company that has completely transformed the tourism market in recent years and has also positioned itself as one of the most prominent and recognized platforms worldwide in the tourism industry. . Nowadays the internet and technology have revolutionized the world, what was previously unthinkable, that is, manipulating a business via the web, is now more than possible; In this research, we will be able to identify the aforementioned changes in all dimensions and especially beyond the business, we will cover the entire population that does not have the appropriate knowledge for the real estate business and the optimization of their finances in accommodation services in a way informal. Therefore, many ingenious entrepreneurs take advantage of technology, such as network communications media, from which new companies are born or existing ones are transformed, making them more profitable, more efficient and effective, both for the employer and the user. who wishes to take the offered service. Airbnb had an impact on many traditional systems, entrepreneurs and traditional cities, who never imagined that there was such a practical business model to do it and that at the same time it would be profitable for those who start in it. Airbnb, the apartment rental platform between individuals, is today a successful and expanding company worldwide. Although it enjoys great prestige, it has also been the subject of criticism from the tourism industry, which emphasizes the economic benefits that this application acquires and the negative economic impact on hotels. The objective is to execute a research project to evaluate the level of profitability of this platform and the tourism industry within the economic sector, using the strategies developed for the comprehensive management of administrative and accounting services in the accommodations of Santa Marta, taking into account The goal is for the population to have knowledge of the entire world that revolves around these digital platforms, and at the same time have fundamental strategies to carry out and make decisions and profits from this business opportunity. It is evident that, for these strategies, keeping a good accounting of your income, expenses and costs and having the ideal knowledge in the sector will help you be an excellent businessman and of course obtain important profits in the short, medium or long term.